Science, Education and Social Vision of Five Nineteenth Century Headmasters - Bottomley, David Theodore (Curtin University, 2018)
From Waterloo to the First World War, British teachers associated with four selected schools expected their students to improve social conditions in Britain. They used advanced teaching methods, provided world views and opportunities for informal learning. Their school costs were above average. Robert Owen, Richard Dawes and Frederick Sanderson became associated with conservative groups which eventually undid their attainments. George Edmondson, then Charles Willmore, free of opposition, continued until market forces closed their school.